Fine-Scale Dating And Chemical Variations Of Deep-Sea Ferromanganese Crusts In The Western And Central Pacific - Akira Usui (International Marine Minerals Society, 2002)
Fine-scale geochemical, mineralogical, and structural variations in ferromanganese crusts are believed to be the long-range records of paleoceanographic conditions and geological events on the small to global scales in the world oceans, which is useful in reconstructing marine environment. The chemical profiles of thick hydrogenetic ferromanganese crusts and nodules were determined by ICP/ES at 2-3 mm intervals at several locations over the Japanese Islands, Magellan Seamounts, Marshall Islands, and South Pacific Basins, together with Be-10 dating. We found general trend of Co enrichment (or high ratio of Co/Mn) in the upper layers of crusts, or outer layers of nodules, which formed in younger period probably after the late Miocene. This general trend of higher Co concentration in the surface may be true over the western to the Pacific, but local variations in growth patterns and shorter-range fluctuations in chemistry and structure were found as well. The growth rate is sometimes three times faster at the shallower depth even in a single seamount. The in-depth fluctuation of Co is well correlated with the ratios Mn/Fe ratio and Ce/La, suggesting changes in redox conditions during the growth of hydrogenetic ferromanganese crusts.